THE INFLUENCE OF GROWTH MINDSET ON SELF-ADJUSTMENT IN NEW STUDENTS - Siti Sandya; Yuarini Wahyu Pertiwi (Adisam Publisher, 2025)
This research aims to determine the effect of Growth Mindset on adjustment to new students. Growth mindset is an individual's effort to improve his or her quality through effort, hard work, and the experience he or she has. This research uses quantitative methods, with regression and correlation studies. The population used in this research was undergraduate students class of 2023 with a total of 92 respondents used in the research. Based on the results of analysis with Spearman's rho correlation there is a correlation coefficient value of 0.463, this shows a positive relationship between Growth Mindset and Self-Adjustment. A positive relationship means that the higher the Growth Mindset, then the higher the Self-Adjustment, and the lower the self-adjustment, then the Growth Mindset Getting lower. Students with a growth mindset tend to have a better level of adjustment in academic, social, emotional and institutional attachment. Apart from that, it was found that growth mindset contributed an influence of 26.2% to the adjustment of new students at Bhayangkara. University, Greater Jakarta.